2022
DOI: 10.3390/pathogens11111254
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Canine Adenovirus Type 1 (CAdV-1) Infection in Domestic Dogs in Southern Italy

Abstract: Canine adenovirus type 1 (CAdV-1) is the causative agent of a systemic and potentially fatal viral disease of domestic and wild canids. In Italy, CAdV-1 infection has also been occasionally described in dogs, but information on the epidemiology and its genomic features is still limited. A study was conducted on 291 dogs suspected of infectious gastrointestinal disease. Samples collected from dogs in southern Italy between 2017 and 2020 were analyzed. Virological and histopathological assays were carried out. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…They reported that 2.1% of the total dogs were infected with CAdV‐1, either alone or co‐infected with other viruses (CPV‐2/CCoV). Additionally, the dogs that tested positive for CAdV‐1 were all dead stray dogs 24 . Also, in a study conducted in Turkey, Bulut et al.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They reported that 2.1% of the total dogs were infected with CAdV‐1, either alone or co‐infected with other viruses (CPV‐2/CCoV). Additionally, the dogs that tested positive for CAdV‐1 were all dead stray dogs 24 . Also, in a study conducted in Turkey, Bulut et al.…”
Section: Discussionmentioning
confidence: 96%
“…After the introduction of CAdV-1 vaccines, ICH largely disappeared, but over the past decade, disease has re-emerged in Italy, Switzerland and the United States. 9,19,22,23 Co-infection by CAdV-1 and CCoV 22,24 or canine parvovirus 10,24 has been reported in dogs. A study was conducted in 291 dogs in southern Italy between 2017 and 2020, on the prevalence of canine gastrointestinal pathogens of viral origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the high CAdV-1 rates obtained in this study may be explained by the remarkable resistance in the environment of this virus that, similar to CPV-2, can act as natural booster in dogs that come into contact with it. CAdV-1 infection has occasionally been described in Italy both in wild animals and in dogs [ 24 , 31 , 58 , 59 , 60 ], as elsewhere. In addition, vaccines for infectious canine hepatitis contain CAdV-2 (and not CAdV-1) that, together with Bordetella bronchiseptica and parainfluenza viruses, is one of the major agents of the Canine Infectious Respiratory Disease Complex (CIRDC, formerly known as kennel cough or canine infectious tracheobronchitis).…”
Section: Discussionmentioning
confidence: 99%
“…The infection mainly affects dogs and other carnivores and damages the kidneys, liver, and eyes. Since the middle of the last century, its incidence in the canine population has been drastically reduced worldwide, thanks to systematic vaccination [ 17 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%